Eksplorasi Konsumsi Kopi dan Potensi Ketergantungan pada Mahasiswa FKM UIN Sumatera Utara - Nabila Fatila; Ana Nurjanah; Nailah Nafisah; Nadia Putri Manik; Muhammad Dio Kurniawan Takasima; Reni Agustina Harahap (Jurnal Kesehatan Amanah, 2026)
Coffee consumption among university students has increased and has become an integral part of both academic and social activities. The caffeine content in coffee is believed to improve concentration, maintain mood, and reduce drowsiness. However, repeated coffee consumption may also lead to negative effects, including mild psychological dependence in some individuals. This study aimed to explore coffee consumption and the potential for dependence among students of the Faculty of Public Health, UIN Sumatera Utara. The study employed a qualitative method with a descriptive approach. The participants consisted of 30 active students who regularly consumed coffee and were selected using purposive sampling. Data were collected through in-depth interviews using semi-structured interview guidelines and analyzed through thematic analysis. The findings revealed that coffee consumption among students was influenced by academic demands, late-night study habits, psychological factors, social environments, and hanging-out culture. Students consumed coffee to improve concentration, maintain mood, reduce sleepiness, and support the completion of academic tasks. In addition, some students considered coffee an important part of their lifestyle and social interactions. The study also identified the potential for mild psychological dependence, characterized by decreased concentration, increased drowsiness, and reduced enthusiasm when coffee was not consumed. These findings indicate the importance of providing education regarding safe and healthy caffeine consumption among university students to prevent adverse effects associated with excessive coffee intake.